Towards Perpetual Brand-Consumer Relationships - Julian R. K. Wichmann; Nico Wiegand; Werner J. Reinartz (Marketing Review St.Gallen, 2021)
Branded Product Platforms (BPPs) orchestrate the joint value creation by its platform participants to occupy consumers' entire need categories. They thereby evolve the brand-consumer relationship, allowing brands to foster intimate and perpetually ongoing interactions with consumers that transcend the traditional customer journey.
Keywords: 650